2022
DOI: 10.1101/2022.06.30.498285
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wnt7a Suppresses Adipogenesis of Skeletal Muscle Mesenchymal Stem Cells and Fatty Infiltration Through the Alternative Wnt-Rho-YAP/TAZ Signaling Axis

Abstract: Intramuscular fatty infiltration in muscle injuries and diseases, caused by aberrant adipogenesis of fibro-adipogenic progenitors, negatively impacts function. Intramuscular delivery of Wnt7a offers a promising strategy to stimulate muscle regeneration but its effects on adipogenic conversion of fibro-adipogenic progenitors remain unknown. Here we show that Wnt7a inhibits adipogenesis of FAPs through the alternative Wnt-Rho-YAP/TAZ signaling that subsequently upregulates the canonical Wnt pathway. Furthermore,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…To probe for the underlying mechanism driving Vcam1+ FAP-promoted adipogenesis, we explored the RNA-seq profiles of Vcam1+ and Vcam1-FAPs for Wnt signaling, which has been reported to be a critical inhibitor of adipogenesis 33,34 . Indeed, Wnt signaling pathways were significantly downregulated in Vcam1+ FAPs compared to Vcam1-FAPs (Figure 4a).…”
Section: Sfrp1 Regulates Vcam1+ Fap Adipogenic Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…To probe for the underlying mechanism driving Vcam1+ FAP-promoted adipogenesis, we explored the RNA-seq profiles of Vcam1+ and Vcam1-FAPs for Wnt signaling, which has been reported to be a critical inhibitor of adipogenesis 33,34 . Indeed, Wnt signaling pathways were significantly downregulated in Vcam1+ FAPs compared to Vcam1-FAPs (Figure 4a).…”
Section: Sfrp1 Regulates Vcam1+ Fap Adipogenic Differentiationmentioning
confidence: 99%
“…We also observed decreased Wnt signaling in Vcam1+ FAPs. Canonical Wnt signaling is a well established inhibitor of adipogenesis 34 . In a murine muscular dystrophy model, Reggio et al demonstrated that the canonical Wnt/Gsk/B-catenin signaling axis inhibited FAP adipogenic differentiation 40 .…”
Section: Scrna-seq and Scatac-seq Identify Nr3c1 As A Candidate Cell-...mentioning
confidence: 99%
“…Activation of the WNT5a/β-catenin signaling pathway can prevent the differentiation of FAPs into adipocytes, thereby inhibiting ectopic fat deposition in muscle ( Reggio et al., 2020 ). WNT7a also inhibits the differentiation of FAPs toward adipocytes and fatty infiltration through the WNT-Rho-YAP/TAZ signaling axis in a β-catenin-independent manner ( Fu et al., 2023 ). During skeletal muscle regeneration, activated FAPs secrete interleukin (IL)-6, which stimulates the proliferation and differentiation of SCs, thereby promoting skeletal muscle repair ( Joe et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%